Compact high‐current diode laser nanosecond‐pulse source with high efficiency and 13 µJ output energy. Issue 1 (1st January 2015) - Hoffmann, Th.; Klehr, A.; Liero, A.; Erbert, G.; Heinrich, W.
Abstract : A compact gain‐switched nanosecond diode laser pulse source at 920 nm with an output energy of 13 µJ is presented. The developed nanosecond electronic driver is based on GaN transistors and controlled by transistor–transistor logic compatible input pulses. A peak current of more than 430 A for 20–50 ns‐long pulses with a repetition rate up to 100 kHz and an electrical efficiency of more than 50% is reached. About 50 ns optical pulses with a peak power of 250 W (13 µJ) are generated with a tapered ridge waveguide bar with 29 emitters. The rise and fall time of the pulses is about 13 ns.